OPTIMASI PENJADWALAN PROYEK KONSTRUKSI MENGGUNAKAN METODE LEAST COST SCHEDULING - Santi Dwi Rahmawati; I Nyoman Dita Pahang Putra; Anna Rumintang Nauli (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
Along with the development era, more and more construction projects are built to meet all human needs, ranging from residential homes to business premises or the place of service of the general public. In a project generally have a plan and implementation schedule for the implementation of the project can be run in accordance with the desired plan. Therefore, project management is a strategy that needs to be done in achieving the efficiency and effectiveness of a company. Some of the kinds of methods that can be used to accelerate a construction project can be used to optimize cost and schedule. One of the methods that can be used is the method of Least Cost Analysis. The results of the analysis using the method of least cost scheduling, namely for the duration of the acceleration to be 54 days, 10 days faster than the normal duration. As for the cost of acceleration, i.e. Rp. 3,407,624,263.72 is greater than the normal cost of Rp. 2,856,611,621.08. The difference in the cost of the project acceleration with the normal cost is Rp. 551,012,642.64. Based on efficiency then the project is not worth it to do the acceleration.